Pendidikan Islam di Bawah Bayang Kolonialisme: Kurikulum, Tantangan dan Perkembangannya - yanas, aufa ni'matul wafa aufa binti ahmad; Safia, Ghanis Fatiha Namya; Astuti, Nita Yuli (EDUSHOPIA : Journal of Progressive Pedagogy, 2025)
This study thoroughly investigates how Islamic education, particularly its curriculum, adapted and developed under colonial pressures and interventions. In addition, it identifies the various problems faced. The data in this study were collected from primary sources, such as colonial archival documents, religious manuscripts, and modern writings. Secondary sources, such as books and scholarly journals, supported the data with a qualitative approach with desk studies and historical methods. The data collection process involved searching, verifying, and extracting relevant information from historical texts. Qualitative content analysis identified patterns and themes, and interpretation of historical texts contextualized the results in time and space. The study shows that colonial policies significantly changed the Islamic education curriculum through direct repression and forced modernization. The institution faced many major problems. These included standardization of education, limited institutional autonomy, and attempts to eliminate Islam from the curriculum. Nevertheless, Islamic education showed a remarkable ability to adapt. It created various defense methods, internal reforms, and curriculum innovations that combined modern elements with Islamic traditions. This ensured that Islamic education survived and flourished during the colonial period.